Piwi reduction in the aged niche eliminates germline stem cells via Toll-GSK3 signaling - Kun-Yang Lin (Nature Portfolio, 2020)
Retrotransposons are known to be involved in aging. Here the authors show that the retrotransposon silencer Piwi contributes to germline stem cell loss during aging in Drosophila.